Gaya Bangunan Rumah Dalam Analisis Stratifikasi Sosial Masyarakat Pedesaan Jawa - Eko Murdiyanto (Jurnal Dinamika Sosial Ekonomi, 2002)
The phenomena of hose style changed in rural community happened together with urban culture influence as a core of consequence of migration. Migration can increase household income change rural style. The effect is changing rural community as a part societes. The migration influence social stratification.Key Words : Migration, House Style, Part Societies, Social Stratification.